Eficácia de diferentes métodos de orientação em promover o uso racional de dentifrício fluoretado por pais com baixo letramento em saúde bucal: ensaio controlado e randomizado - Renata Kézia Pereira dos Anjos (2023)
Knowing the literacy level of the population allows professionals to develop strategies so that individuals' decisions can be more conscious, responsible, and correct. In Dentistry, the rational use of fluoride can be impaired if the guidelines for daily use are not understood. Therefore, this study aimed to evaluate the effectiveness of different guidance methods in developing the ability of parents/guardians with low oral health literacy (OHL) for the rational use of fluoridated toothpaste. A controlled and randomized trialwas carried out. The study included 100 parents and/or legal guardians of children aged 0 to 5 years enrolled in public schools in Belo Horizonte, literate, with Portuguese as their native language and who were classified as having a low level of OHL by the BREALD-30 instrument (score 0-21). The randomized allocation sequence was generated by a researcher blinded to the type of intervention with: 1) Written guidance; 2) Oral guidance; 3) Written guidance with photographic image; 4) Oral guidance with photographic image and 5) Audiovisual guidance. Parents received guidance from the researcher regarding the fluoride concentration (1000 ppm of fluoride) and the recommended amount of toothpaste to be placed on the toothbrush (equivalent to a smear). The weight of dentifrice was measured using a precision scale. The primary outcome of the study was the percentage of approximation between the amount of toothpaste applied to the toothbrush by the parent/guardian after the intervention and the recommended amount of toothpaste (0.125g). The Wilcoxon, Mann-Whitney and Kruskal-Wallis tests were used to test associations between toothpaste volume (initial and final weight in relation to ideal weight). One-way ANOVA was used to test the association between approximation percentage and intervention group. A significance level of 5% was adopted. Data were analysed using the SSPS version 20.0 program (Statistical Package for the Social Sciences, IBM®). There was a significant reduction in the amount of toothpaste dispensed on the toothbrush after the instructions, in all intervention groups (p≤0.05). The approximation percentage values for group 1 (written guidance) were significantly different from groups 2 (oral guidance) and 3 (written guidance + photographic image) (p< 0.001). Group 5 (audiovisual) was different from groups 3 (written guidance + photographic image) and 4 (oral guidance + photographic image) (p< 0.001). The audiovisual orientation group presented the best results, with a better percentage of approximation to the ideal value. Educational strategies in oral health for children with parents classified as having a low level of OHL should associate the use of illustrations or demonstrations for a better understanding and execution of the guidelines.